Ultra-Poor Graduation Model: Evaluasi Implementasi Program di Indonesia - Rusdi Hamka Lubis (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2024)
The Extreme poverty remains a major challenge in Indonesia’s socio-economic development. One innovative approach implemented to address this issue is the Ultra-Poor Graduation Model (UPGM). This model is designed as a phased intervention to help extremely poor households achieve economic self-sufficiency through six key components: participant targeting, consumption support, productive asset transfer, skills training, intensive coaching, and access to financial services. This study evaluates the implementation of UPGM in Indonesia by examining adapted programs such as the Graduation Program under PKH (Conditional Cash Transfer Program) and empowerment initiatives by non-governmental organizations (NGOs), including Rumah Zakat and PKPU Human Initiative. The evaluation results indicate increases in income, ownership of productive assets, and positive changes in participants’ consumption patterns. However, several challenges remain, such as accurate targeting of beneficiaries, limited human resources for coaching, and the risk of participants falling back into poverty after the program ends. Comparisons with UPGM implementation in Bangladesh and Ethiopia highlight the importance of intensive mentoring, integration with social protection programs, and market access to ensure long-term program sustainability. Therefore, strengthening policies, continuous monitoring, and cross-sector collaboration are essential for optimizing UPGM as a strategy to eradicate extreme poverty in Indonesia.